The U.S. policy towards Central Asia - Luguusharav, Byambakhand (Journal of International Studies, 2022)
After the 9/11 terrorist attacks, the United States launched military operations and deployed its troops in Afghanistan. In August 2021, the United States withdrew the last of its troops from Afghanistan, ending its military presence there after nearly 20 years, a result of the “Agreement for Bringing Peace for Afghanistan” signed with the Taliban. According to expectations by the experts whose eyes are on Central Asia, the withdrawal of U.S. troops from Afghanistan would bring some changes to the U.S. policy towards the region which is close to Afghanistan. However, the U.S. has to focus on the European theatre, as Russia launched a “special operation” in Ukraine by justifying its action as a “crusade” against neo-Nazis. Russia’s military actions have forced Washington to shift its attention to transatlantic security, leaving a vacuum in Central Asia to be filled by Russia and China. In the first part of the article, the author seeks to analyze the geopolitical importance of Central Asia and the competition of great powers to expand their influence in the region. As stated in the Constitution of the United States, as the Chief Executive, the president has the authority in shaping the foreign policy of the country, so the second part of the article is for the discussion of the U.S. presidents’ policies toward Central Asia. At the end of the article, as a researcher, the author seeks to share her take on the possible changes in Washington’s policy in Central Asia with respect to President Joe Biden’s decision to withdraw U.S troops from Afghanistan. Төв Азид чиглэсэн АНУ-ын бодлого Хураангуй: Есдүгээр сарын 11-ний террорист халдлагын дараа АНУ цэргийн ажиллагаа явуулж, Афганистанд цэргээ байрлуулсан Талибуудтай байгуулсан “Афганистанд энхийн гэрээний”-ний үр дүнд 2021 оны наймдугаар сард АНУ Афганистанаас сүүлчийн цэргээ гаргаж, 20 орчим жилийн дараа цэргээ гаргасан юм. Төв Азийг судалдаг шинжээчдийн үзэж байгаагаар, АНУ нь цэргээ Афганистанаас гаргаснаар тус улстай ойр орших Төв Азийн бүс нутгийн талаарх АНУ-ын бодлогод тодорхой өөрчлөлт гарах төлөвтэй байна. Гэсэн хэдий ч Оросын Украинд явуулж буй дайн байлдааны үйл ажиллагаанаас үүдэн АНУ Европын аюулгүй байдлыг анхаарахаас өөр аргагүй байдалд ороод байгаа юм. Үүнээс болоод Төв Азид Орос, Хятад нь давамгайлах нөлөөгөө хадгалах боломжтой. Зохиогч өгүүллийн эхний хэсэгт Төв Азийн геополитикийн ач холбогдол, бүс нутагт нөлөөгөө тэлэхийн төлөөх их гүрнүүдийн өрсөлдөөнд дүн шинжилгээ хийлээ. Түүнчлэн АНУ-ын Үндсэн хуульд зааснаар тус улсын ерөнхийлөгч гүйцэтгэх засаглалын тэргүүний хувьд улс орныхоо гадаад бодлогыг тодорхойлоход чухал үүрэгтэй тул өгүүллийн хоёрдугаар хэсэгт АНУ-ын үе үеийн ерөнхийлөгчийн Төв Азийн талаар баримталж буй бодлогыг авч үзсэн. Өгүүллийн төгсгөлд АНУ-ын цэргийг Афганистанаас гаргах тухай Ерөнхийлөгч Ж.Байдены шийдвэртэй холбогдуулан Вашингтоны Төв Азийн талаарх бодлогод гарч болзошгүй өөрчлөлтийн талаар судлаачийн байр сууриа хуваалцсан юм. Түлхүүр үгс: Төв Ази, АНУ-ын бодлого, Афганистан, геополитик, ашиг сонирхол